<<The>> Samye monastery - Dbang-phyug-rgyal-po,Lokesh Chandra,Tucci, Giuseppe (International Academy of Indian Culture, 1961)
Historischer Führer durch das Kloster von Samye
Keywords: Samye (Monastery : Cha-nang hsien; China)